APPLICATION OF SIMULATION RESEARCH TO ANALYSE THE PRODUCTION PROCESS IN TERMS OF SUSTAINABLE DEVELOPMENT - ZACHCIAŁ, Agnieszka; JARDZIOCH, Andrzej (Applied Computer Science, 2022)
Sustainable development is an very important idea nowadays and it influences on many factors. It is very important to focus on the goals of sustainable development and implement them both in industry and in everyday life. The aim of the article is to analyse the impact of implementing an automatic conveyor belt transport system between the stands of an exemplary assembly line on sustainable development in economic and environmental terms. The analyzed production process consists of one production line with six assembly stations. The efficiency of individual design solutions and electricity consumption were adopted as the evaluation criteria. To compare the two processes, a simulation analysis was performed in the Plant Simulation program. First chapter is the introduction to the article. The second chapter describes the current applications of simulation tests. The third chapter describes the production system that is improved by adding conveyors. The next chapter compares the processes with and without the use of conveyors and presents how much energy must be used additionally by implementing conveyor belts, but also what energy savings can be obtained by installing additional stop sensors. The fifth chapter presents the conclusions: the conducted research allowed concluding that the implementation of conveyor belts affects a higher number of finished products at the same time as the transport of components is manual. However, the best solution is to use conveyors with stop sensors, and the power consumption is then low and more profitable for the enterprise.